2D Semiconducting Metal–Organic Framework Thin Films for Organic Spin Valves. (29th November 2019) - Song, Xiaoyu; Wang, Xinyue; Li, Yusen; Zheng, Chengzhi; Zhang, Bowen; Di, Chong‐an; Li, Feng; Jin, Chao; Mi, Wenbo; Chen, Long; Hu, Wenping
Abstract: 2D conductive metal–organic frameworks (2D c ‐MOFs) feature promising applications as chemiresistive sensors, electrode materials, electrocatalysts, and electronic devices. However, exploration of the spin‐polarized transport in this emerging materials and development of the relevant spintronics have not yet been implemented. In this work, layer‐by‐layer assembly was applied to fabricate highly crystalline and oriented thin films of a 2D c ‐MOF, Cu3 (HHTP)2, (HHTP: 2, 3, 6, 7, 10, 11‐hexahydroxytriphenylene), with tunable thicknesses on the La0.67 Sr0.33 MnO3 (LSMO) ferromagnetic electrode. The magnetoresistance (MR) of the LSMO/Cu3 (HHTP)2 /Co organic spin valves (OSVs) reaches up to 25 % at 10 K. The MR can be retained with good film thickness adaptability varied from 30 to 100 nm and also at high temperatures (up to 200 K). This work demonstrates the first potential applications of 2D c ‐MOFs in spintronics. Abstract : Hoch kristalline und ausgerichtete Dünnschichten aus dem 2D‐leitfähigen MOF Cu3 (HHTP)2 wurden auf einer ferromagnetischen La0.67 Sr0.33 MnO3 (LSMO)‐Elektrode schichtweise aufgebaut. Ein großer Magnetowiderstand von 25 % wurde für dieses organische LSMO/Cu3 (HHTP)2 /Co‐Spinventil erreicht. Das Material ist vielversprechend für Anwendungen in der Spintronik.